2021
DOI: 10.3390/vaccines9080809
|View full text |Cite
|
Sign up to set email alerts
|

Agent Based Model of Anti-Vaccination Movements: Simulations and Comparison with Empirical Data

Abstract: Background: A realistic description of the social processes leading to the increasing reluctance to various forms of vaccination is a very challenging task. This is due to the complexity of the psychological and social mechanisms determining the positioning of individuals and groups against vaccination and associated activities. Understanding the role played by social media and the Internet in the current spread of the anti-vaccination (AV) movement is of crucial importance. Methods: We present novel, long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(97 reference statements)
1
10
0
1
Order By: Relevance
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 included studies, 18 (40%) studies reported misinformation across all 3 categories [ 27 - 29 , 35 - 37 , 45 , 48 , 49 , 51 , 55 , 57 , 58 , 60 - 62 , 67 , 68 ], 9 (20%) studies reported only on conspiracies [ 26 , 30 , 33 , 42 , 44 , 46 , 53 , 54 , 56 ], 6 (13%) studies were concerned specifically with medical misinformation [ 25 , 34 , 38 , 43 , 63 , 64 ], and 12 (27%) studies reported on COVID-19 vaccine misinformation or antivaccine discourse without going into further detail [ 31 , 35 , 39 - 41 , 47 , 52 , 59 , 65 , 66 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…60,63 One study looked at anti-vaccine discussions on both Reddit and the Polish social media platform Interia. 64 Two studies examined YouTube videos in English 44 and in Spanish. 52 One US study looked at English language TikTok messages 47 and another US study examined English language messages on the American social media platform Parler.…”
Section: Highmentioning
confidence: 99%
“…22,31,35,39,60,61 12 studies reported on COVID-19 vaccine misinformation or anti-vaccine discourse without going into further detail. 28,32,[36][37][38]44,47,50,58,[62][63][64] We identified 19 studies that made assumptions about the effects of social media misinformation on vaccine hesitancy (Table 4). The evaluation of the certainty of evidence of these 19 studies that measured the "Association between social media misinformation and COVID-19 vaccine hesitancy" was classified as moderate or low-moderate according to GRADE in two cases.…”
Section: Highmentioning
confidence: 99%
“…Sobkowicz and Sobkowicz (2021) present an excellent framework for understanding motivations and undercurrents that seem to be driving vaccine hesitancy and refusal:
“The impact of the pandemic on everyday life and the economy is significant on a global scale. The combination of fears related to health with the severe effects of social and economic lockdowns creates an emotional landscape in which distrust of the medical industry in general and anti‐vaccination arguments, in particular, can easily take hold.
…”
Section: Vaccine Hesitancy and Refusalmentioning
confidence: 99%